(untitled) (Світ фінансів, 2017)
Ібрагімов М. Р. Шляхи удосконалення оподаткування власності в сучасних умовах розвитку місцевого самоврядування. Обґрунтовано необхідність реформування майнового оподаткування в Україні. Запропоновано основні напрямки удосконалення оподаткування майна в контексті зміцнення фінансових ресурсів органів місцевого самоврядування. Ibrahimov M. The ways of property taxation improvement in the modern terms of local self-government development. Principal reasons of necessity of reformation of property taxation are expounded in Ukraine. Basic directions of improvement of taxation of property are described in the context of financial resources of organs of local self-government.